Applying the Reproducing Kernel Method to Fractional Differential Equations with Periodic Conditions in Hilbert Space - Hoda Saky; Saeid Abbasbandy; Elyas Shivanian (Journal of Mathematics)
In this article, the reproducing kernel method is presented for the fractional differential equations with periodic conditions in the Hilbert space. This method gives an approximate solution to the problem. The approximate and exact solutions are displayed in the form of series in the reproduction kernel space. In addition, we provide an error analysis for this technique. The presented method is tested by some examples to show its precision.